Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Safety Pada Toko Cahaya Teknindo - Farah Riezka Marhan; Arman Syah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - The purpose of this study was to determine the role of price (X1) and product quality (X2) on consumer purchasing decisions (Y) on Toko Cahaya Teknindo products. The method used in this study is quantitative with a quantitative descriptive approach and the population in this study was 98 consumers. The sampling technique used was proportional random sampling using a questionnaire technique method with a sample of 98 respondents. The analysis tool used instrument testing, classical assumption testing, regression testing, autocorrelation testing and coefficient of determination and hypothesis testing. The results of the price variable significantly influenced purchasing decisions with a t count of 7,518> t table 0.1985 and a Sig. <0.05 (0.000 <0.05). The results of the product quality variable on purchasing decisions with a t count of 5.949 > t table 0.1985 and a Sig. <0.05 (0.000 <0.05). The results of the price and product quality variables simultaneously have a significant effect on purchasing decisions with a calculated f value of 28.021 > 3.093 and a Sig. value < 0.05 (0.000 < 0.05). The results of the study concluded that there was a significant influence both partially and simultaneously between the role of price and product quality on purchasing decisions on Cahaya Teknindo Store products.